Implementing Total Quality Management To Strengthen Vocational Education Quality: A Case Study At SMK Budi Tresna Muhammadiyah Cirebon - Wita Noviyanti; Ria Yulia Gloria; Iis Arifudin (IJGIE (International Journal of Graduate of Islamic Education), 2026)
Education must continuously adapt to social transformation and the evolving demands of the industrial sector, particularly in vocational education, where graduate competencies should align with workforce expectations. Total Quality Management (TQM) provides a comprehensive management approach that emphasizes customer focus, continuous improvement, and the involvement of all stakeholders to enhance educational quality. This study aims to analyze the implementation of TQM in strengthening the quality of vocational education at SMK Budi Tresna Muhammadiyah Cirebon and to identify both its achievements and implementation challenges. A descriptive qualitative case study approach was employed, with data collected through observations, semi-structured interviews, and documentation involving the principal, teachers, students, and industry partners. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that TQM has contributed to improving curriculum relevance to industry needs, strengthening teacher professionalism through continuous professional development, enhancing stakeholder satisfaction, and fostering stronger collaboration with industry partners in curriculum development and competency assessment. However, the implementation of TQM remains constrained by limited qualified human resources, inadequate practical learning facilities, and restricted financial support, which hinder the sustainability of continuous quality improvement. These findings suggest that effective TQM implementation in vocational schools requires strong leadership commitment, systematic stakeholder collaboration, continuous investment in human and physical resources, and strategic partnerships with industry to establish a sustainable quality culture and improve institutional competitiveness.